Two new species of Rhaphiomidas (Diptera: Mydidae) - Rogers, Rick; van Dam, Matthew H. (Zootaxa, 2007)
Two new species of Mydidae, Rhaphiomidas pachyrhynchus sp. nov. and Rhaphiomidas moapa sp. nov. are described and illustrated here for the first time. Rhaphiomidas pachyrhynchus represents the southeastern most record of the genus. Notes on the adult ecology of R. moapa are given.